(3MUQ GdbhGWYs - (3SfO Hf Ydjs ((3MGLi Ydi GdQGRi s)
(3ChdgG (B:s
(3gPG cJGH BNQ hLOfGg dSfO Hf Ydi ai MUQ GdbhGWY , cGf ` QMeg Gddg ` Ufag ChdkG , Ke Yed cJGHg GdcHjQ GdPi bHd gPG (B[ (3GdbhGWY (B] (3fcJH gfG (B: (3bGd SfO Hf Ydi bO cKQ ZdW GdbGFdjf ai OdGFd GdehGdjO s
(3BNQgG (B:s
(3aEf cGf ai SYO ef ebGHdI GdTeS hEf cGf ai GdTYGY ddehdhO YeQ Je s
(3Vef eLehY , JQJjHgG (B: (3ef U (B335 - (3U(B339s
(3HgG fXGe GdJYbjHIs
(3cJHJ fbdkG Yf fSNI LeYgG EHQGgje GdMGSH Gdedci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI(B759(3g`s
(3HChd GdeLehYI Jedc SfI (B1249(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs